The Impact of Peer-mediated Intervention on Children with Special Needs in Inclusion Classroom - Muqoddam, Faqihul; Hendriani, Wiwin (Fakultas Psikologi UIN Syarif Hidayatullah Jakarta, 2020)
Systematic review aims to analyze the impact of interventions that mediated by peers on children with special needs in an inclusion setting. The review was conducted with the search keywords